Insight on esterase from Pseudomonas aeruginosa strain S3 that depolymerize poly(lactic acid) (PLA) at ambient temperature. (April 2020) - Noor, Hazrat; Satti, Sadia Mehmood; Din, Salah ud; Farman, Muhammad; Hasan, Fariha; Khan, Samiullah; Badshah, Malik; Shah, Aamer Ali
Abstract: Pseudomonas aeruginosa strain S3 exhibited high esterolytic activity against poly (lactic acid) (PLA) at environmental temperature ( 30 °C). A comprehensive study was conducted for optimization of physico-chemical parameters for high-throughput esterase production using Plackett–Burman Design and Central Composite Design. PLA degradation by Pseudomonas aeruginosa strain S3 was confirmed during preliminary studies using Fourier Transform Infrared Spectroscopy (FTIR) and scanning electron microscopy (SEM). The date obtained from statistical optimization demonstrated interactive action of inoculum size with peptone, yeast extract and Tween 20 was more influential towards esterase activity. The following medium constituents were optimized for maximum esterase production [(g/L) Glucose, 0.8; Peptone, 10.5; Yeast extract, 15; MgSO4 .7H2 O, 0.3; Sodium citrate, 4; CaCl2, 1; NaCl, 1; FeSO4 .7H2 O, 1; Inoculum size 75 mL and Tween 20, 3.8 mL (v/v)]. The molecular weight of purified esterase was approximately 35 kDa with apparent K m and V max values, i.e., K m 12.38 μM and V max 769.23 U/mg, respectively. The enzyme showed stability over a broad range of pH (3–10) and temperature (20–40 °C). The activity of the purified enzyme was significantly enhanced by non-polar detergents (Tween 80 and Triton-X100), glycerol as well as both mono and divalent cations (Co +2 and K +1 ). Hydrolysis of PLA films with purified esterase released oligomers of medium chain length (n = 6–13), reaffirming the biodegradation potential of Pseudomonas aeruginosa strain S3 against PLA. The results obtained from the study demonstrate the potential of our strain and its enzymes in development of high efficient system of PLA biodegradation and recovery processes. Highlights: Esterolytic activity of Pseudomonas aeruginosa strain S3 was determined against PLA Statistical optimization of physico-chemical parameters was performed for high-throughput esterase production. Esterase was purified to homogeneity and molecular weight was determined. The stability to different phyico-chemical parameters as well as kinetics studies were performed. Degradation of PLA by purified esterase and degradation products were analyzed through LCMS.